Kelembagaan Non-Formal (Kelompok Tani Bina Satu) dalam Masyarakat Petani Tomat di Desa Parabubu, Kecamatan Mego - Magdalena Selvi Irawati Kwuta; Margaretha Maurita Delang; Mikhaela Novianti; Yerianus Dami Rea; Fortunata Marianus Moa Eko (Mikroba : Jurnal Ilmu Tanaman, Sains Dan Teknologi Pertanian, 2025)
Non-formal institutions, such as farmer groups, play a strategic role in increasing farmer capacity and strengthening agricultural production systems at the village level. This study aims to analyze the role, function, and institutional dynamics of the Bina Satu Farmer Group in supporting tomato farmers in Parabubu Village, Mego District. A descriptive qualitative approach was used, with data collection techniques including observation, in-depth interviews, and documentation. The results indicate that the Bina Satu Farmer Group serves as a learning platform, a collaborative unit, and a liaison between farmers and external institutions. This institution functions in disseminating information on tomato cultivation technology, strengthening access to production inputs, and enhancing farmers' bargaining power in marketing. However, several weaknesses were identified, such as low member participation in routine meetings and limited managerial skills among administrators. Overall, the existence of this farmer group has significantly contributed to increasing the knowledge, productivity, and independence of tomato farmers in Parabubu Village.